Effect of seven oriental herbs mixture (Jogyeongbohyeoldan) on the restoration of ovarian aging in aged mice - Jong-Kil Joo; Chae-Hak Lim; MinJung Park; HyeonJeong Kim; Chang-Woon Kim; Chul-Hee Yoon; Jeong-Eun Yoo; BoSun Joo (Clinical and Experimental Obstetrics & Gynecology)
Purpose of Investigation: Ovarian aging remains a difficult problem in infertility treatment. The traditional oriental herbs have been widely used for female infertility treatment. This study investigated the effect of seven oriental herbs mixture (Jogyeongbohyeoldan, JBD) on ovarian aging and oocyte quality in aged and premature ovarian failure female mice. Materials and Methods: C57BL/6 female mice aged 12 months (natural ovarian aging, NOA) were administered once daily with JBD of 15 mg/kg (n = 7) and 30 mg/kg (n = 7) of body weight for 4 weeks using syringe with oral zoned needle. The control group (n = 7) was treated with normal saline. After final treatment of JBD, follicle counts were evaluated by hematoxylin and eosin (H&E) staining, and ovarian mRNA expressions of genes related to PI3K/mTOR (4E-BP1, S6K1, RPS6) and Hippo (MST1, LATS1) signaling pathway, and angiogenesis (VEGF, visfatin, and SDF-1α) were examined by quantitative real-time PCR. In the second experiment, NOA and premature ovarian failure mice (POF) were treated with JBD (n = 7 each), and were superovulated with PMSG and hCG, followed by mated with male. Numbers of zygotes ovulated and embryo development rate were examined. In the third experiment, a total of 18 NOA female mice and 24 POF mice were administered with JBD and mated with males for 2 weeks, and then the pregnancy outcome was monitored up to 20 days. Results: JBD significantly increased numbers of primordial, primary, secondary, and antral/mature follicles, and ovarian mRNA expression of 4EBP1, S6K1, RPS6, MST1, LATS, VEGF, and SDF-1α. Also JBD significantly increased numbers of zygotes retrieved and embryo development rate to blastocyst in NOA and POF mice compared to controls (P < 0.05). JBD treatment significantly increased pregnancy outcome including number of live birthed pups in both NOA and POF mice. Conclusions: These results suggest that JBD can restore ovarian aging and improve ovarian function, ovarian response and oocyte quality in aged mice. It is suggested that this beneficial effect may be related to an increase in ovarian expression of genes associated with PI3K/mTOR and Hippo signaling pathways and angiogenesis.